Weight Gain and Treatment Interruptions with Second-Generation Oral Antipsychotics: Analysis of Patients with Schizophrenia or Bipolar I Disorder. (April 2021) - Doane, Michael J.; Bessonova, Leona; Mortimer, Kathleen; Cheng, Harry; Donadio, Gregory; Brecht, Thomas; O'Sullivan, Amy K.; Cummings, Hannah; McDonnell, David; Meyer, Jonathan M.
Abstract: Among patients with schizophrenia (SZ) and bipolar I disorder (BD-I) treated with second-generation antipsychotics (SGAs), clinically-significant weight gain (CSWG) and treatment interruptions (TIs) are challenges that may result in morbidity/mortality. CSWG and TIs were assessed among patients who initiated oral SGAs of moderate-to-high weight gain risk (no exposure to index SGAs/first-generation antipsychotics for =12 months) using medical records/claims (OM1 Data Cloud; January 2013-February 2020). Outcomes included CSWG (=7% increase in baseline weight) and TIs (switches [to SGAs of low weight gain risk/long-acting injectables] or discontinuations [no SGAs for >30 days]). Descriptive analyses included proportions of patients with CSWG and TIs, and median time to these outcomes. Approximately three-quarters of patients were overweight/obese at baseline (SZ: N=8, 174; BD-I: N=9, 142). Within 3 months of SGA initiation, 12% of all patients experienced CSWG. For patients on treatment with index SGAs for >6 months (SZ: 29%; BD-I: 27%), 28% (SZ) and 30% (BD-I) experienced CSWG during follow-up. Median time to CSWG was 14 weeks. CSWG results were numerically similar among patients with SZ and BD-I. Over 96% of patients had TIs during follow-up (median time of 12 [SZ] and 13 [BD-I] weeks). Among patients with CSWG and subsequent TIs and weight measurements, 74% did not return to baseline weight after interrupting treatment; the remainder returned to baseline weight with median times of 38 (SZ) and 39 (BD-I) weeks. Results suggest that most patients with CSWG do not return to baseline weight after stopping treatment with oral SGAs of moderate-to-high weight gain risk. Funding. Alkermes, Inc.